ChemInform Abstract: Pathways Leading to 3‐Amino‐ and 3‐Nitro‐2, 3‐dideoxy Sugars: Strategies and Synthesis. Issue 41 (19th September 2013) - Ding, Feiqing; Cai, Shuting; William, Ronny; Liu, Xue‐Wei
Abstract Review: 249 refs.